Use of carnosine in the prevention of cardiometabolic risk factors in overweight and obese individuals: study protocol for a randomised, double-blind placebo-controlled trial. Issue 5 (13th May 2021) - Menon, Kirthi; Cameron, James D; de Courten, Maximilian; de Courten, Barbora
Abstract : Introduction: Carnosine, an over the counter food supplement, has been shown to improve glucose metabolism as well as cardiovascular risk factors in animal and human studies through its anti-inflammatory, antioxidative, antiglycating and chelating properties. The aim of this study is to establish if carnosine supplementation improves obesity, insulin sensitivity, insulin secretion, cardiovascular risk factors including arterial stiffness and endothelial function, and other risk factors related to diabetes and cardiovascular disease in the overweight and obese population. Methods and analysis: Fifty participants will be recruited to be enrolled in a double-blind randomised controlled trial. Eligible participants with a body mass index (BMI) between 25 and 40 kg/m 2 will be randomly assigned to the intervention or placebo group. Following a medical review and oral glucose tolerance test to check eligibility, participants will then undergo testing. At baseline, participants will have anthropometric measurements (BMI, dual X-ray absorptiometry and peripheral quantitative CT scan), measurements of glucose metabolism (oral glucose tolerance test, intravenous glucose tolerance test and euglycaemic hyperinsulinaemic clamp), cardiovascular measurements (central blood pressure, endothelial function and arterial stiffness), a muscle and fat biopsy, physical activity measurement, liver fibroscan, cognitive function and questionnaires to assess dietary habits, sleep quality, depression, and quality of life. Following baseline assessments, participants will be randomised to either 2 g carnosine or placebo for 15 weeks. In the 15th week, all assessments will be repeated. The preplanned outcome metric is the change between baseline and follow-up measures. Ethics and dissemination: This study is approved by the Human Research Ethics Committee of Monash Health and Monash University, Australia. Trial registration number: NCT02686996 .